Proposal to extend access to loans for serious illnesses using open data - Frédéric Planchet; Édouard Debonneuil; Marie Péju (Risks, 2022)
In France, access to a loan requires one to obtain loan insurance and the presence of a pathology in the applicant may be a reason for refusal. Improving knowledge of health risks and pooling risks are two methods of broadening access to loans. We attempt to analyse these possibilities using open data and risk pooling scenarios. We find that the removal of medical selection can be ensured if the current framework is adjusted. We also demonstrate how to use open data to estimate loan insurance premiums for a variety of diseases. We take two examples: breast cancer and type 1 diabetes. Broadening access to borrowing would be beneficial for patients and for the development of the economy associated with these projects.
Keywords: 330; borrower insurance; mortality; serious illnesses